1984
DOI: 10.1016/0166-445x(84)90012-2
|View full text |Cite
|
Sign up to set email alerts
|

Joint effects of a mixture of 14 chemicals on mortality and inhibition of reproduction of Daphnia magna

Abstract: The toxicity to Daphnia magna of a mixture of 14 aquatic pollutants with several chemical structures and probable modes of action was determined. The joint effect of this mixture on acute mortality was compared with the effects on inhibition of reproduction. The joint toxicity in the reproduction test was lower in comparison with the mortality test. This study supports the idea that the potential for addition is reduced when more specific sublethal toxicity criteria are studied. Although the joint toxicity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 10 publications
5
54
0
1
Order By: Relevance
“…On the other hand, acute toxicity testing using daphnids, (e.g., Daphnia magna), is a common bioassay used internationally for screening toxicity of chemicals and monitoring of effluents and contaminated waters (Persoone et al, 2009). D. magna has been recommended as a standard test organism by many international organizations (e.g., ISO, 1996 andOECD, 2004) and has ISSN 2157-6076 2015 www.macrothink.org/jbls 230 been used routinely in toxicological studies (Biesinger and Christensen, 1972;Hermens et al, 1984;De Schamphelaere et al, 2004). Hence, it is important to include both V. fischeri and D. magna in a battery of tests designed for protecting the aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, acute toxicity testing using daphnids, (e.g., Daphnia magna), is a common bioassay used internationally for screening toxicity of chemicals and monitoring of effluents and contaminated waters (Persoone et al, 2009). D. magna has been recommended as a standard test organism by many international organizations (e.g., ISO, 1996 andOECD, 2004) and has ISSN 2157-6076 2015 www.macrothink.org/jbls 230 been used routinely in toxicological studies (Biesinger and Christensen, 1972;Hermens et al, 1984;De Schamphelaere et al, 2004). Hence, it is important to include both V. fischeri and D. magna in a battery of tests designed for protecting the aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…However, toxicity in natural ecosystems typically does not result from single toxicant exposure, but is rather a result of exposure to mixtures of toxicants (Altenburger et al, 1996;Gardner et al, 1998) and therefore mixture toxicity has been a subject of ecotoxicological interest for several decades (Hermens et al, 1984;Altenburger et al, 1996;Silva et al, 2002;Backhaus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(3) for the stress aggregation needs to take cognisance of the knowledge about the interaction among stresses. For toxic substances, true synergism among the substances appears to be rare (Hermens et al, 1984a;1984b;Calamari and Vighi, 1992) although it has been reported (Broderius and Kahl, 1985). Additivity of toxicity occurs more often than true synergism or supra-additivity.…”
Section: Aggregating Diverse Stressorsmentioning
confidence: 99%